Molecular Characterization of Coxiella Burnetii: An Emerging Zoonosis with Therapeutic Update and Future Perspectives - Arslan Habib; Riffat Iqbal; Zeeshan Ashraf; Dominic Kwesi Quainoo; Misbah Bano; Amjad Ali; Muhammad Shehzad; Ghulam Jaffar (Issues and Development in Health Research Vol. 7, 2021)
Q fever is an infectious disease caused by Coxiella burnetii which is an obligatory intracellular parasite. Globally Q fever is a widespread zoonosis. It is characterized by headaches, sudden fever and atypical pneumonia. In the rural environment, the main reservoir includes goats, sheep, cows, dogs, cats and rabbits. The main reservoir of this bacteria is considered domestic animals. They produce in a large number in amniotic fluid and placenta during childbirth. The main route of infection is inhalation. Q fever can cause both acute and chronic infection, mostly asymptomatic in humans and animals. Inactivated whole-cell bacteria vaccination strategy has been performed which provides effective outcomes in humans and animals but many side effects have been observed. The recombinant vaccine has been developed and provides many effective results in experimental conditions. One of the major challenges is the lack of accurate diagnosis facilities if it becomes possible, the prognosis of disease development can be reduced. Direct detection of bacteria is the accurate test for the diagnosis. Different procedures are involved in this method such as immunodetection, PCR amplification and shell vial cell culture. Due to the severe infectivity of C. burnetii all these procedures require a biosafety level 3 lab and qualified staff. Q fever is a challenging disease for scientists to reduce its burden globally. The prevalence of Q fever can have a significant economic impact on animal trade, reproduction and the commercialization of different animal products. The review discloses the Coxiella burnetii genome, the clinical manifestation of Q fever as well as emerging issues, diagnosis, treatment, prevention and future directions.